Barriers and facilitators of infectious disease outbreak reporting: a One Health scoping review - Amish Talwar; Md. Abu Sayeed; Tambri Housen; Rebecca Katz; Martyn D. Kirk (One Health Outlook)
Abstract Background Addressing the barriers to outbreak reporting is critical to prevent future outbreaks from becoming epidemics or pandemics. As most emerging infectious diseases are zoonotic in origin, this requires understanding the barriers affecting both the human and animal health sectors. However, previous reviews of outbreak reporting barriers have only looked at barriers with respect to humans or animals independently. Therefore, we undertook a One Health approach to holistically understand the impact of outbreak reporting barriers across the human health, animal health, and environmental sectors. Methods We conducted a scoping review of the peer-reviewed and grey literature to identify barriers and facilitators for outbreak reporting affecting human health, animal health, and the environment. We selected studies that identified discrete barriers or facilitators at the subnational, national, and international levels using quantitative research, qualitative research, mixed methods, or reviews. We extracted information on publication information, barriers, and facilitators, and we thematically summarised our findings. Results Among 5,177 records examined, we selected 151 matched parameters for data abstraction and analysis. The most employed methodology was qualitative (56 studies), and the East Asia and Pacific (43 studies) and Sub-Saharan Africa (40 studies) regions were the most studied. Only 45 studies evaluated outbreak reporting with respect to a specific disease. Identified outbreak reporting barriers and facilitators fell under three major themes: technical; economic, political, and bureaucratic; and behavioural and social. We found substantial evidence for technical barriers to outbreak reporting across all regions and sectors and resistance to reporting among agricultural producers. However, evidence for additional barriers, particularly barriers to environmental reporting, is more limited. Conclusions This study affirms the importance of building countries’ technical capacity to report outbreaks. However, it also indicates the need to sensitize reporters and government officials on the importance of outbreak reporting. A comprehensive understanding of the full breadth of outbreak reporting barriers and facilitators across human health, animal health, and the environment otherwise remains incomplete, with critical implications for ongoing and future outbreaks. Future studies should endeavour to fill these gaps in the evidence base as part of an integrated One Health strategy to improve the outbreak reporting process.